Automation and sectoral reallocation - Dennis C. Hutschenreiter; Tommaso Santini; Eugenia Vella (SERIEs - Journal of the Spanish Economic Association, 2022)
Empirical evidence in Dauth et al. (J Eur Econ Assoc, 2021) suggests that industrial robot adoption in Germany has led to a sectoral reallocation of employment from manufacturing to services, leaving total employment unaffected. We rationalize this evidence through the lens of a general equilibrium model with two sectors, matching frictions and endogenous participation. Automation induces firms to create fewer vacancies and job seekers to search less in the automatable sector (manufacturing). The service sector expands due to the sectoral complementarity in the production of the final good and a positive wealth effect for the household. Analysis across steady states shows that the reduction in manufacturing employment can be offset by the increase in service employment. The model can also replicate the magnitude of the decline in the ratio of manufacturing employment to service employment in Germany between 1994 and 2014.
Keywords: E24; J22; J23; O14; O33; 330; Automation; Manufacturing; Matching frictions; Participation; Productivity; Sectoral reallocation; Services; Vacancy creation